Building and Codifying a Measure of Pursue among Advanced Volleyball Players in Iraq - Afrah Baqer Abduljaleel; Luma Sameer Hamoodi (Indian Journal of Forensic Medicine & Toxicology, 2021)
The importance of the study lies in the extent to which the players possess pursue and what it contains interms of cooperation, coordination and integration in the roles that lead to achieving common goals amongthe players, which is reflected in their solidarity by performing the required tasks, whether in the training orcompetition process.The problem arises: Do advanced volleyball players rely on discipline to achieve the team’s common goals,both in training and competition?The objective of the research was to: Building and codifying the pursue scale for advanced volleyballplayers, as well as setting standard levels for the advanced volleyball players’ pursue scale.The researchers used the descriptive approach in the survey method because it is more appropriate to theobjectives of the research and the nature of the problem. The research community consists of the IraqiPremier League volleyball players for the season (2019-2020), whose number is (196) players. And all theresearch sample was selected intentionally.As for the most important conclusions: It was to find a measuring tool to build and standardize the pursue ofadvanced volleyball players. The research sample was distributed over five levels of the scale of pursue foradvanced volleyball players. While the most important recommendations were: The researcher recommendsusing a symmetry scale on all players in other team games.